Nanomechanical Assessment of Bone Surrounding Implants Loaded for 3 Years in a Canine Experimental Model - Anchieta, Rodolfo B. [UNESP]; Guimarães, Márcia V.M.; Suzuki, Marcelo; Tovar, Nick; Bonfante, Estevam A.; Atria, Pablo; Coelho, Paulo G. (Elsevier, 2018)
Purpose This work evaluated the nanomechanical properties of bone surrounding submerged and immediately loaded implants after 3 years in vivo. It was hypothesized that the nanomechanical properties of bone would markedly increase in immediately and functionally loaded implants compared with submerged implants. Materials and Methods The second, third, and fourth right premolars and the first molar of 10 adult Doberman dogs were extracted. After 6 months, 4 implants were placed in 1 side of the mandible. The mesial implant received a cover screw and remained unloaded. The remaining 3 implants received fixed dental prostheses within 48 hours after surgery that remained in occlusal function for 3 years. After sacrifice, the bone was prepared for histologic and nanoindentation analysis. Nanoindentation was carried out under wet conditions on bone areas within the plateaus. Indentations (n = 30 per histologic section) were performed with a maximum load of 300 μN (loading rate, 60 μN per second) followed by a holding and unloading time of 10 and 2 seconds, respectively. Elastic modulus (E) and hardness (H) were computed in giga-pascals. The amount of bone-to-implant contact (BIC) also was evaluated. Results The E and H values for cortical bone regions were higher than those for trabecular bone regardless of load condition, but this difference was not statistically significant (P >.05). The E and H values were higher for loaded implants than for submerged implants (P <.05) for cortical and trabecular bone. For the same load condition, the E and H values for cortical and trabecular bone were not statistically different (P >.05). The loaded and submerged implants presented BIC values (mean ± standard deviation) of 57.4 ± 12.1% and 62 ± 7.5%, respectively (P >.05). Conclusion The E and H values of bone surrounding dental implants, measured by nanoindentation, were higher for immediately loaded than for submerged implants.